Kontestasi Identitas dan Kesalehan Anak Usia Dini Islam dalam Animasi Nussa - Mustakim, Bagus (Islamic Early Childhood Education Study Program, Faculty of Tarbiyah and Education, UIN Sunan Kalijaga Yogyakarta, 2019)
Discussion of the piety of early childhood, currently in the shadow of an ideological debate of various political, social and religious identities. This kind of ideological debate is increasing along with the expansion of global social media networks in the digital age. In this ideological debate, a phenomenal animated film called